The Impact of Aquatic Salinization on Fish Habitats and Poor Communities in a Changing Climate : Evidence from Southwest Coastal Bangladesh - Dasgupta, Susmita; Huq, Mainul; Mustafa, Md. Golam; Sobhan, Md. Istiak; Wheeler, David (Elsevier, 2018)
Fisheries constitute an important source of livelihoods for tens of thousands of poor people in the southwest coastal region of Bangladesh, and they supply a significant portion of protein for millions. Among the various threats fisheries in the southwest coastal region will face because of climate change, adverse impacts from increased aquatic salinity caused by sea level rise will be one of the greatest challenges. This paper investigates possible impacts of climate change on aquatic salinity, fish species habitats, and poor communities using the salinity tolerance ranges of 83 fish species consumed in the region and aquatic salinity in 27 alternative scenarios of climate change in 2050. The results provide striking evidence that projected aquatic salinization may have an especially negative impact on poor households in the region. The estimates indicate that areas with poor populations that lose species are about six times more prevalent than areas gaining species.